2023
DOI: 10.3390/ijms24076762
|View full text |Cite
|
Sign up to set email alerts
|

WAX INDUCER 1 Regulates β-Diketone Biosynthesis by Mediating Expression of the Cer-cqu Gene Cluster in Barley

Abstract: Plant surface properties are crucial determinants of resilience to abiotic and biotic stresses. The outer layer of the plant cuticle consists of chemically diverse epicuticular waxes. The WAX INDUCER1/SHINE subfamily of APETALA2/ETHYLENE RESPONSIVE FACTORS regulates cuticle properties in plants. In this study, four barley genes homologous to the Arabidopsis thaliana AtWIN1 gene were mutated using RNA-guided Cas9 endonuclease. Mutations in one of them, the HvWIN1 gene, caused a recessive glossy sheath phenotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…The CER gene family contributes to the production of cuticle wax and has a vital function in stress mitigation [ 12 ]. The CER gene family has been found across the genome in a range of plant species, including Castanea mollissima [ 32 ], apple [ 29 ] and passion fruit ( Passiflora edulis ) [ 31 ], and functionally described in (A) thaliana [ 43 ], Barley [ 44 ], Brachypodium distachyon [ 45 ], and (B) napus [ 46 ]. However, the CER genes in cotton ( G. hirsutum ) have not yet been studied.…”
Section: Discussionmentioning
confidence: 99%
“…The CER gene family contributes to the production of cuticle wax and has a vital function in stress mitigation [ 12 ]. The CER gene family has been found across the genome in a range of plant species, including Castanea mollissima [ 32 ], apple [ 29 ] and passion fruit ( Passiflora edulis ) [ 31 ], and functionally described in (A) thaliana [ 43 ], Barley [ 44 ], Brachypodium distachyon [ 45 ], and (B) napus [ 46 ]. However, the CER genes in cotton ( G. hirsutum ) have not yet been studied.…”
Section: Discussionmentioning
confidence: 99%
“…The nud KO lines are known to have lower root weight and shorter length relative to win1 KO lines under normal conditions [28]. It has been reported that at later stages of development, nud KO and win1 KO lines do not differ from the WT line in key growth characteristics, except for a reduction in 1000-grain weight in hull-less nud KO lines, which has been attributed to the absence of lemmas [13,14,28].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, two-row spring barley (H. vulgare L.) cv. GP has been chosen as donor material for targeted mutagenesis (inactivation) of genes HvNUD [13] and HvWIN1 [14] by means of the Cas9/gRNA system. In the present work, to assess salt tolerance of the obtained KO barley plants, three nud KO lines (nud 01-4, nud 05-4, and nud 07-1) and three win1 KO lines (win1 17-4-14, win1 25-2-2, and win1 25-2-18) were utilized, each carrying different mutation types (deletion, insertion, or their combinations).…”
Section: Plant Modelsmentioning
confidence: 99%
See 2 more Smart Citations